The Relationship of mental health awareness on mental well-being, job performance, and employee retention. - Calixto, Aliahna Jean J. Carpio, Princess Allana B . Eudela, Princess, Louella Y. Nacuspad, Jenny. Quinto, Tracy A. Rocha, Jeshua Leur A. Vergara, Jenina Marie V. 4 0 16; 5
ABSTRACT This research, conducted in November 2024 investigates the relationship between mental health awareness on mental well-being, job performance, and employee retention in Metro Manila's food service industry. With growing concerts for mental health in the workplace, this research aims to understand how mental health awareness aRects employees. Using descriptive and correlational research design, data were collected using a survey with a 4point Likert scale to measure the employee's perception. The results showed that mental health awareness is linked with improved mental well-being, better job performance, and increased employee retention. Findings suggest that while employees recognize the importances of mental health awareness, there is still an opportunity to improve training programs and resources that would support the mental well-being, job performance, and employee retention of the employees. Recommendations emphasize the need for accessible and eRective mental health training programs, active employee involvement, and a workplace culture that reduces stigma that is essential for enhancing workplace.
Business Research: (BSBA major inHuman Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2